Separation of terpenes from lemon essential oil by selective fractionation under a vacuum - Frolova, Natalia; Ukrainets, Anatoliy; Sylka, Iryna; Niemirich, Oleksandra; Kuzmin, Oleg (My University, 2019)
The paper reports basic modern methods for isolating terpenes, outlines the advantages and reasons for this particular technological processing of essential oils, specifically lemon oil. The qualitative composition and quantitative ratios of components in lemon essential oil were determined by gas chromatography on a packed column (the stationary phase-dinonylphthalate). Based on the chromatographic profile, it was found that the key component of the oil is monoterpene d-limonene (70.60±4.61 %), which masks a harmonious manifestation of lemon flavor.The paper reports results from theoretical calculations of selective fractionation under a vacuum that have been tested at a laboratory installation for the fractional distillation of essential oils, which simulates a full cycle of fractionation. The basic nodes of the installation were aligned with the schemes of universal plants that are common in industry. The optimal modes for the selection of terpenes and terpenoid factions are given, namely the value for the limit and working reflux number, pressure, and boiling temperature ranges.The fraction of terpene, selected at a cube temperature from 67 °C to 70 °C, under a pressure of 2.64 kPa at a reflux ratio of 1:3, makes up 30.0 % by weight. The fraction of terpenoids, selected at a cube temperature from 84 °C to 96 °C, under a residual pressure from 0.33 to 0.66 kPa and at a reflux ratio of 1:14, makes up 60.0 % by weight. Following the organoleptic study, it was established that the terpene fraction has a lemon flavor, due to the high content (80.0 %) of limonene, with notes of bergamot (β-myrcene ‒ 5.12 %). Among other terpenoids, citral adds a muscat tone to the aroma, which, together with geraniol and linalool, acquires a noble aroma of citrus with a fine floral note.All fractions of essential oils should be used in the food and cosmetic technology because the fraction of terpenes could be a valuable component in the creation of original composite fragrances.Розкрито основні сучасні методи виділення терпенів, вказано переваги та причини цього технологічного перероблення ефірних олій, зокрема лимонної. Якісний склад і кількісні співвідношення компонентів лимонної ефірної олії визначено газохроматографічним методом на насадковій колонці (нерухома фаза – динонілфталат). З даних хроматографічного профілю з’ясовано, що ключовим компонентом олії є монотерпен d-лімонен (70,60±4,61 %), що маскує гармонійний прояв лимонного аромату.
Keywords: кафедра технології ресторанної і аюрведичної продукції; lemon essential oil; fractionation; deterpenation; gas chromatography; packed column; limonene; лимонна ефірна олія; фракціонування; детерпенізація; газова хроматографія; насадкова колонка; лімонен; лимонное эфирное масло; фракционирование; детерпенизация; газовая хроматография; насадочная колонка; лимонен